2015
DOI: 10.1021/acs.biomac.5b01289
|View full text |Cite
|
Sign up to set email alerts
|

pH-Reversible Cationic RNase A Conjugates for Enhanced Cellular Delivery and Tumor Cell Killing

Abstract: Intracellularly-acting therapeutic proteins are considered promising alternatives for the treatment of various diseases. Major limitations of their application are low efficiency of intracellular delivery and possible reduction of protein activity during derivatization. Herein, we report pH-sensitive covalent modification of proteins with a histidine-rich cationic oligomer (689) for efficient intracellular transduction and traceless release of functional proteins. Enhanced Green fluorescent protein (EGFP), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…However, RNases can have distinct but not always successful outcomes in several cellular organelles, such as endosomes, lysosomes, ER and the trans-Golgi network (136). Thus, many studies have been performed to unveil the intracellular routing of extracellular RNases once internalized by endocytosis, and the relative results indicated that diverse RNases, such as ONC or BS-RNase as well as RNase A, RNase 1, or ANG follow different cellular pathways within one another, as described or proposed in several reports (32, 118, 120, 128, 130132, 135).…”
Section: Crucial Steps For Cytotoxic Extracellular Rnases To Exert Thmentioning
confidence: 91%
See 1 more Smart Citation
“…However, RNases can have distinct but not always successful outcomes in several cellular organelles, such as endosomes, lysosomes, ER and the trans-Golgi network (136). Thus, many studies have been performed to unveil the intracellular routing of extracellular RNases once internalized by endocytosis, and the relative results indicated that diverse RNases, such as ONC or BS-RNase as well as RNase A, RNase 1, or ANG follow different cellular pathways within one another, as described or proposed in several reports (32, 118, 120, 128, 130132, 135).…”
Section: Crucial Steps For Cytotoxic Extracellular Rnases To Exert Thmentioning
confidence: 91%
“…More recently, an interesting strategy to intracellularly internalize RNases was proposed: three cationic amine-reactive linkers were attached to RNase A, and the stability of these conjugates was pH-dependent. Therefore, the endocytic vesicles' acidic environment led to the release of high cytosolic amounts of RNase A to make its concentration high enough to overcome the RI binding capacity and become cytotoxic (135).…”
Section: Crucial Steps For Cytotoxic Extracellular Rnases To Exert Thmentioning
confidence: 99%
“…However, demonstration that activity was retained was not explored. Delivery of functional enzymes has been demonstrated by Schepartz and Wagner [201,202]. Wagner, Lächelt and coworkers developed a three-arm cationic star succinoyl tetraethylenepentamine conjugated with a tetraethylene glycol linker by a pH-responsive aminated methyl maleic anhydride bond [201].…”
Section: Cellular Level Interactions and Behaviorsmentioning
confidence: 99%
“…Delivery of functional enzymes has been demonstrated by Schepartz and Wagner [201,202]. Wagner, Lächelt and coworkers developed a three-arm cationic star succinoyl tetraethylenepentamine conjugated with a tetraethylene glycol linker by a pH-responsive aminated methyl maleic anhydride bond [201]. The protein star conjugate showed some diffuse fluorescence of enhanced green fluorescent protein (eGFP) at a 1 μM of protein, and was demonstrated to induce apoptosis through the similar delivery of RNase A star conjugate.…”
Section: Cellular Level Interactions and Behaviorsmentioning
confidence: 99%
“…We have previously demonstrated that drug‐loaded rigid nanoparticles (NPs) show advantages with respect to improved cellular uptake and better cancer therapeutic efficiency than their soft counterparts . To improve the endo/lysosomal escape of nanovectors after internalization, the presence of cationic surface charge could facilitate disruption of the endo/lysosomal membrane . However, it is critical to shield the positive surface charge during blood circulation to avoid non‐specific interaction with serum proteins and negatively charged molecules presented on the cell membrane .…”
Section: Introductionmentioning
confidence: 99%